A change of circumstance : a Simon Serrailler case - Hill, Susan, 1942- (Hill, Susan, 1942- Simon Serrailler crime novels., 2022)
DCS Simon Serrailler has long regarded drugs ops in Lafferton as a waste of time. Small-time dealers are picked up outside the local secondary school, they don't have any information about those higher up the chain, they're given a fine or a suspended and away they go. And rinse and repeat. But when the body of a 22-year-old drug addict is found in neighbouring Starley, the case pulls Simon into a whole new way of running drugs. The foot soldiers? Vulnerable local kids like Brookie and Olivia, who will give Simon a bitter taste of this new landscape. It is a harsh winter at home as well as work. Simon's GP sister Cat and her husband Kieron (also Simon's boss) are struggling with medical dramas big and small. A trip to Bevham General on her rounds sets off alarm bells for Cat, and a visit from her son Sam as he tries to work out if his midwifery course is right for him coincides with a threat to their beloved family dog. Simon is working hard, but he's restless, wondering what's next. There's nothing new going on for him in Lafferton, but sometimes the familiar holds surprises, too...